Practical skills of persons with vision impairment - Anđelković, Marija; Vučinić, Vesna; Gligorović, Milica; Maksić, Jasmina (Vojnosanitetski pregled, 2023)
Background/Aim. The acquisition of practical skills (PS), as well as adaptive behavior (AB) in general, is affected by an array of personal and environmental factors. The aim of this study was to determine the level of acquisition of practical adaptive skills (PAS) among adults with vision impairment (VI), in comparison to the norms among the general population and with regard to the vision status (low vision and blindness), age of vision loss onset, gender, age, living arrangements, education, and employment status. Methods. Seventy-nine (62.2%) participants who were blind and forty-eight (37.8%) participants with low vision and typical intellectual abilities voluntarily took part in the study. The respondents were aged from 19 to 60 years, with a mean age of 36.1 ± 11.8 years. PAS were assessed using the PS domain which is part of the Adaptive Behavior Assessment System II – ABAS II. Results. The scores achieved in the skill areas of the PS domain range from extremely low to average. Extremely low scores were detected in the Work skill area, while for the skill areas of Community use, Home living, and Health and safety, the scores were below average, and average scores were noted in the Self-care skill area. The degree of PS acquisition among participants with VI depended primarily on the vision status, but a significant connection with living arrangements and employment status was also established. Conclusion. Persons with VI showed significant limitations in the area of PS, which indicates the need for support programs designed to foster the development of self-reliance.